PENGARUH BUDAYA TRI HITA KARANA, AKUNTABILITAS, DAN PENGAWASAN INTERNAL TERHADAP KINERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA DI KECAMATAN NUSA PENIDA - Ni Komang Sumadi; Ni Luh Devi Srikasih; Ni Made Dewi Kansa Putri (UNHI Press, 2022)
Employee performance affects the success of a company, including financial institutions, both bank and non-bank financial institutions such as the Village Credit Institution (LPD). The purpose of this study was to determine the effect of Tri Hita Karana Culture, Accountability, and Internal Control on the Performance of Village Credit Institutions (LPD). This research was conducted at 45 Village Credit Institutions (LPD) in Nusa Penida District with a population of 180 people. The sampling method used is a non-probability sampling method with purposive sampling technique. The total sample taken is 150 people who are directly related to the performance of the Village Credit Institution (LPD) employees, namely the LPD chairman, secretary, treasurer and employees who have worked for more than 1 year. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that the Tri Hita Karana Culture, Accountability, and Internal Control have a significant positive influence on the Performance of the Village Credit Institution (LPD) Employees in Nusa Penida District.